PENGARUH KEPUASAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN PENGGUNA JASA EMKL : Studi Kasus di PT. MITRA UTAMA INDOTRANS SURABAYA - Alya Dita Sarasati; Sugiharto; Bambang Karnain (Fakultas Ekonomi Universitas 45 Surabaya, 2022)
This study is useful to determine the effect of satisfaction and trust given to customer loyalty at PT. Mitra Utama Indotrans Surabaya. The population in this study amounted to 60 respondents, while the sampling technique used the census method because the population and sample were the same, and the data collection technique used was a questionnaire, while the data analysis technique used the explanatory research method using statistical analysis with regression, correlation, and determination testing. , and hypothesis testing. The results of this study that satisfaction has a significant effect on customer loyalty, hypothesis testing is obtained t count > t table or (5,273> 2.002) . Trust has a significant effect on customer loyalty, hypothesis testing is obtained t count > t table or (4.473> 2.002). Satisfaction and trust simultaneously have a significant effect on customer loyalty with the regression equation Y=0,325+0,483X1+0,381X2+0,43, hypothesis testing is obtained F count > F table (38.805>3.159).